Online gambling: Cross-border aspects and potential risk of divorce - Setiyawan, Deni; Fauzia, Ana; Mohamed, Muhammad Azimuddin; Pratama Hapsari, Ifahda; Mashdurohatun, Anis; Jaya Wardana, Dodi (Universitas Ahmad Dahlan, 2025)
Introduction to the Problem: Online gambling produces cascading social harms (debt, mental distress, and family conflict) that are surfacing in Indonesian divorce cases. Yet core enforcement gaps persist because gambling platforms, servers, and payment rails are frequently offshore and evidence is digital and volatile. Existing tools in the ITE Law and the Criminal Code lag behind these modalities. Purpose/Study Objectives: To analyze how cross-border features of online gambling undermine Indonesian criminal and family-law responses, and to propose an integrated reform agenda that links criminal accountability with family protection. Design/Methodology/Approach: Normative legal research combining statutory and conceptual analysis with comparative insights (licensed regimes such as Australia/UK; prohibition/ambiguous regimes) and illustrative Indonesian Religious Court decisions referencing gambling-driven marital breakdown. Findings: Indonesia’s response is hampered by three enforcement deficits: (1) Platform/finance dependence: foreign digital platforms and domestic payment intermediaries (banks, e-wallets, telecoms) enable chip-based and crypto-denominated flows that current doctrine barely reaches; (2) Digital-evidence fragility: logs, metadata, and accounts are transient or hosted abroad, while preservation and admissibility standards and forensics capacity remain under-specified; and (3) Limited cross-border reach: narrow MLAT/extradition coverage and dual-criminality barriers where gambling is legal overseas. These deficits help explain a growing footprint of gambling in Indonesian divorce pleadings and judicial reasoning, even when causation is indirect (asset dissipation, coercive financial control, persistent conflict). Comparative practice shows courts can recognize gambling-related “wastage” in property division and maintenance, while regulators can harden payment and advertising controls. Overall, the paper finds that doctrinal silos between criminal/ITE rules and the Marriage Law weaken both enforcement and family protection. Paper Type: Research Article